THE INFLUENCE OF LEMON (Citrus Limon (L.)) IRON ION (Fe) REMOVAL ON STAINLESS STEEL ORTHODONTIC WIRE - Chiquiteta Mariska Chairunnisa; R Rama Putranto; Moh Husnun Niam (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Lemons consist of 5-8% citric acid, have a pH of around 2.74. Drinks that have a critical pH of 5.5 can be said to be acidic drinks. Acidic drinks have the potential to cause corrosion of teeth and dental materials, one of which is stainless steel orthodontic wire. Stainless steel orthodontic wire is easily corroded, the wire has a composition of 71% Iron (Fe), 18% Chromium (Cr), 8% Nickel (Ni), and 0.2% Carbon (C). Corrosion is caused by the presence of inorganic components that act as electrolyte media that can trigger electrochemical reactions.Method: Each sample was placed on each uninsulated petridish and labeled as a marker. This is done by inserting orthodontic wire which is immersed into the incubator for 3.5 hours at 37℃. Then the sample is taken and the separation between the sample and the solution is carried out. After that, the measurement of Iron (Fe) ions was carried out using the Atomic Absorption Spectrophotomery tool.Result: The results showed the average release of Iron (Fe) ions in the experimental group of lemon juice with a concentration of 25% was 0.067mg/L, a concentration of 50% was 0.090mg/L and a concentration of 100% was 0.135mg/L. The test results obtained using the One Way Anova test showed that there was no significant difference (p>0.05).Conclusion: There was no significant difference in the release of Iron (Fe) ions in stainless steel orthodontic wires between experimental groups, and there was no effect of soaking lemon juice (Citrus Limon (L.)) on the release of Iron (Fe) ions in stainless steel orthodontic wires.